A Note on Cohomological Mirror Symmetry of Toric Manifolds (Communications in Mathematical Research, 2025)
In this note we describe a logarithmic version of mirror LandauGinzburg model for semi-projective toric manifolds and show in an elementary and explicit way that the state space ring of the Landau-Ginzburg mirror is isomorphic to the $\mathbb{C}$-valued cohomology of the toric manifold.